Asset prices under alternative exchange rate regimes - Nicole Aregger (Swiss National Bank, Study Center Gerzensee, 2018)
Motivated by the potential contribution of China's unilateral peg to asset price inflation in the US before the financial crisis of 2007-2009, this paper studies the effect of alternative exchange rate regimes (flexible versus fixed) on the response of asset prices to economic shocks. I use a two-country general equilibrium model with sticky prices and extend earlier work on this topic by making use of a newer method for analyzing portfolio choice in DSGE models. My findings suggest that asset price responses to shocks differ across regimes. In particular, under a fixed regime, which is operated by the foreign country, responses to shocks in the home country are stronger than under a flexible regime. For home asset prices, however, the amplification of shock responses tends to be small. Applied to the US and China, this implies that, under China's prevailing unilateral peg, the Fed's expansionary monetary policy before the crisis resulted in a slightly but not substantially stronger US asset price inflation relative to the one that would have been observed under a floating USD/CNY exchange rate.
Keywords: E42; E44; F41; 330; Asset Price Inflation; Exchange Rate Regime; Endogenous Portfolio Choice; US-China